Hybrid quantum information processing with continuous and discrete variables of light fields - Donati, G (2015)
Quantum correlations play a fundamental role in quantum information science. The variety of their manifestations has become increasingly apparent following the development of novel light sources, protocols and photodetectors. One broad classification identifies two instances of non-classical correlations: particle and mode entanglement. These categories mirror two coexisting descriptions of quantum systems in terms of discrete and continuous variables of the electromagnetic field. The past decades have generated a number of promising results based on schemes which encompass elements from both frameworks, rather than viewing the two descriptions as mutually exclusive. In this context, it is possible to conceive and realise experiments where either the quantum resource or the detection system is 'hybrid'. Optical weak-field homodyne detectors bring together phase sensitivity and photon counting; as such, they represent a detection scheme which works across continuous and discrete variables of the radiation field. In this thesis we present a two-mode weak-field homodyne detection layout with added photon-number resolution and apply it to the study of a split single-photon state and a squeezed vacuum state. As a first test of the capabilities of this system, we investigate the reconstruction of relevant features of a given quantum resource - such as its photon statistics - with our detection scheme. Further, we experimentally demonstrate the observation of an instance of non-classical optical coherence which combines the continuous- and discrete-variable descriptions explicitly. The ability to probe phenomena at the interface of wave and particle regimes opens the way to novel, improved schemes for quantum information processing. From a more fundamental perspective, such hybrid approaches may shed light on the very roots of quantum enhancement.